A Neutral 1D Coordination Polymer Constructed from the NiII Complex of the N‐Phosphorylated Thiourea PhNHC(S)NHP(O)(OPh)2 and Pyrazine: A Single‐Source Precursor for Nickel Nanoparticles. Issue 7 (3rd June 2014) - Babashkina, Maria G.; Safin, Damir A.; Robeyns, Koen; Garcia, Yann
Abstract: The N ‐phosphorylated thiourea PhNHC(S)NHP(O)(OPh)2 (HL ) was synthesized by the reaction of PhNH2 and (PhO)2 P(O)NCS. Reaction of the KL salt, generated in situ, with NiCl2 leads to pale violet [NiL 2 ] with a 1, 3‐ N, S ‐ coordination mode of the ligands. Interaction of [NiL 2 ] with pyrazine (pz) yields the 1:1 coordination polymer [NiL 2 pz] n . An unexpected change in the coordination mode of the phosphorus‐containing ligandsL from 1, 3‐ N, S ‐ to 1, 5‐ O, S ‐ was found in [NiL 2 pz] n upon coordination of additional donor ligands. [NiL 2 pz] n dissolved in tri‐ n ‐octylphosphine (TOP) was decomposed in hot hexadecylamine to give capped face‐centered cubic Ni nanoparticles with an average particle size of 17(2) nm. Abstract : Interaction of [Ni{PhNHC(S)NP(O)(OPh)2 }2 ] with pyrazine (pz) yielded the 1:1 coordination polymer [NiL 2 pz] n, in which the coordination mode ofL changed unexpectedly from 1, 3‐ N, S ‐ to 1, 5‐ O, S ‐[NiL 2 pz] n dissolved in tri‐ n ‐octylphosphine (TOP) is decomposed in hot hexadecylamine to give TOP‐capped face‐centered cubic Ni nanoparticles with an average particle size of 17(2) nm.